Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1109/tuffc.2021.3136620
|View full text |Cite
|
Sign up to set email alerts
|

A Pipeline for the Generation of Synthetic Cardiac Color Doppler

Abstract: Color Doppler imaging is the modality of choice for simultaneous visualization of myocardium and intracavitary flow over a wide scan area. This visualization modality is subject to several sources of error, the main ones being aliasing and clutter. Mitigation of these artifacts is a major concern for better analysis of intracardiac flow. One option to address these issues is through simulations. In this paper, we present a numerical framework for generating clinical-like color Doppler imaging. Synthetic blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Although this remains to be verified, it is likely that a similar strategy could also work with disturbed flows, provided that we have access to Doppler data with their alias-free references. Such ground truths could be obtained by supervised correction, as in this study, and by simulations [25].…”
Section: B Limitations and Perspectivesmentioning
confidence: 99%
“…Although this remains to be verified, it is likely that a similar strategy could also work with disturbed flows, provided that we have access to Doppler data with their alias-free references. Such ground truths could be obtained by supervised correction, as in this study, and by simulations [25].…”
Section: B Limitations and Perspectivesmentioning
confidence: 99%
“…In our team, SIMUS has also recently been applied in the generation of simulated moving ultrasound phantoms and left ventricles to train convolutional neural networks for motion estimation in echocardiography [ 28 , 29 ]. We also simulated clinical-type Doppler-echo cineloops with the future objective to train deep learning algorithms for intracardiac flow imaging [30] . In the same vein, Milecki et al .…”
Section: When Using Simus and Pfield?mentioning
confidence: 99%
“…Another interesting area of research in medical imaging is image generation. Although current research efforts have utilized generative DL for objectives, such as removing artifacts from imaging data [ 32 ], raising the resolution of imaging [ 33 ], producing synthetic imaging datasets [ 34 , 35 ], and improving segmentation outcomes [ 36 ], and the capabilities of generative models are far broader. It has been demonstrated that generative models can convert two biplanar CXRs to a natural-looking chest CT scan and even incorporate synthetic tumoral lesions into normal imaging data [ 37 , 38 ].…”
Section: Synthesismentioning
confidence: 99%